The shortcut why intelligent machines do not think like us - Cristianini, Nello 1968- (CRC Press, 2023)
The Shortcut: Why Intelligent Machines Do Not Think Like Us provides an accessible yet probing exposure of AI in its prevalent form today, proposing a new narrative to connect and make sense of events that happened in the recent tumultuous past, and enabling us to think soberly about the road ahead